Pengembangan E-LKPD dan Instrumen Tes Keterampilan Berpikir Kritis Berbantuan Google Sites pada Materi Termodinamika - Anisya' Destiara Pangesti; Wasis (Universitas Negeri Surabaya, 2025)
This study aims to develop E-LKPD and critical thinking skills test instruments assisted by Google Sites on thermodynamics material to support the development of students' critical thinking skills. This study uses the Research and Development (R&D) method with the ADDIE development model. Data collection methods include expert validation, student response questionnaires, and critical thinking skills tests. Data analysis techniques are carried out using validity analysis, Percentage of Agreement, reliability, difficulty level, discriminatory power, and analysis of the improvement of students' critical thinking skills. The results of the study show that: a). The developed E-LKPD is valid, with a Percentage of Agreement (PoA) value of 90%. b). The developed instrument is also valid and reliable, with an average Percentage of Agreement (PoA) value of 92%. Empirically, it has an easy to moderate level of difficulty and sufficient to good discriminatory power. c) Student responses to E-LKPD are very positive in all aspects and the implementation of learning reaches 100%, so that E-LKPD is very practical, effective and feasible to use. d) Students' critical thinking skills increased with an average N-gain of 0.581, which is in the moderate category. Based on the research results above, it can be concluded that the E-LKPD and the developed test instruments are suitable for use in learning.